Lithium titanate slurry and preparation method thereof, negative electrode and lithium ion battery

By using a combination of mechanical stirring and centrifugal stirring in the preparation of lithium titanate slurry, the problems of poor dispersion and stability of the negative electrode slurry are solved, and the stability of the electrode sheet quality is improved.

CN119764432APending Publication Date: 2025-04-04GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656385.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the quality of the electrode sheet is unstable due to poor dispersion and poor stability of the negative electrode slurry.

Method used

By first mechanically stirring the raw material including a binder, a conductive agent and lithium titanate, the second mechanical stirring is performed, and high-speed stirring is performed in a centrifugal mixer, the material particles are dispersed and refined by centrifugal force to achieve a uniform dispersion effect.

Benefits of technology

The problem of difficulty in dispersing nano lithium titanate materials is effectively solved, the time of the stirring process is shortened, the stability of the lithium titanate slurry is improved, and the quality stability of the electrode sheet is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764432A_ABST
    Figure CN119764432A_ABST
Patent Text Reader

Abstract

The present invention provides a lithium titanate slurry and a preparation method thereof, a negative electrode and a lithium ion battery. The preparation method comprises: subjecting a raw material including a binder, a conductive agent and lithium titanate to a first mechanical stirring to obtain a first mixture; subjecting a raw material including the first mixture and a solvent to a second mechanical stirring to obtain a second mixture; and subjecting the second mixture to centrifugal stirring to obtain a lithium titanate slurry. The present application firstly performs a first mechanical stirring, the purpose of which is to premix the first mixture uniformly; then performs a second mechanical stirring, the function of which is to fully wet the obtained second mixture; and then uses a centrifugal mixer for high-speed stirring, generating a huge shear force to disperse and refine the material particles, and achieve a uniform dispersion effect in a short time, thereby solving the problem of the difficulty in dispersing nano lithium titanate materials, and effectively shortening the time of the stirring process, improving the stability of the lithium titanate slurry, and thus improving the quality stability of the pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium titanate slurry and a preparation method thereof, a negative electrode and a lithium ion battery. Background Art

[0002] Lithium titanate is a spinel structure material. Since the volume change during the charge and discharge process of lithium ion insertion and extraction is very small, almost zero, lithium titanate is called a "zero strain" material. It is an ideal embedded electrode material. Compared with graphite negative electrode materials, lithium titanate materials have good safety and stability. Because of its own high lithium insertion potential, lithium dendrites will not precipitate and pierce the diaphragm during the charge and discharge process, thus avoiding battery short circuit. The structure of lithium titanate determines its good wide temperature resistance. It can charge and discharge normally at -50℃ to +60℃. Lithium titanate has excellent fast charging performance. Lithium titanate contains three-dimensional lithium ion channels, can be charged and discharged at high rates, and has a long cycle life.

[0003] The electronic conductivity of lithium titanate materials is relatively low. Nano-sized lithium titanate materials can effectively shorten the transmission path of electrons and lithium ions, which is beneficial to reduce the transmission impedance of charges, solve the problem of low electronic conductivity of lithium titanate materials, and improve the rapid charging and discharging and low-temperature performance of lithium titanate materials. However, lithium titanate nanomaterials have a relatively high specific surface area, large surface energy, easy agglomeration, and are difficult to disperse during slurry preparation. The wet mixing process currently used takes a long time and the slurry has poor stability, which makes the quality of the corresponding pole piece unstable and is not conducive to large-scale production. Summary of the invention

[0004] The main purpose of the present invention is to provide a lithium titanate slurry and a preparation method thereof, a negative electrode and a lithium ion battery, so as to solve the problem in the prior art that the quality of the pole piece is unstable due to the poor dispersibility and poor stability of the negative electrode slurry.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing lithium titanate slurry is provided, which comprises: subjecting a raw material including a binder, a conductive agent and lithium titanate to a first mechanical stirring to obtain a first mixture; subjecting a raw material including the first mixture and a solvent to a second mechanical stirring to obtain a second mixture; and subjecting the second mixture to centrifugal stirring to obtain lithium titanate slurry.

[0006] Furthermore, the rotation speed of the first mechanical stirring is 500-1000 rpm, and the time of the first mechanical stirring is 0.5-1 h.

[0007] Furthermore, the rotation speed of the second mechanical stirring is 1500-2000 rpm, and the time of the second mechanical stirring is 1-2 hours.

[0008] Furthermore, the rotation speed of the centrifugal stirring is 2500-3000 rpm, and the time of the centrifugal stirring is 3-5 hours.

[0009] Furthermore, the mass ratio of the above-mentioned binder, conductive agent and lithium titanate is 2.5% to 5%: 2.5% to 5%: 90% to 95%; and / or the conductive agent is selected from any one or more of carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, and graphene, and / or the solvent is N-methyl-2-pyrrolidone, and / or the binder is selected from any one or more of PVDF, PTFE and acrylonitrile; and / or the solid content of the lithium titanate slurry is 50 to 60%.

[0010] Furthermore, the preparation method further comprises adjusting the viscosity and fineness of the lithium titanate slurry.

[0011] According to another aspect of the present invention, a lithium titanate slurry is provided. The lithium titanate slurry is prepared by the above-mentioned preparation method.

[0012] Furthermore, the viscosity of the lithium titanate slurry is 8000-15000 mPa·s, and / or the viscosity of the lithium titanate slurry after standing for 10-12 hours is 20000-40000 mPa·s, and / or the fineness of the lithium titanate slurry is 25-35 μm.

[0013] According to another aspect of the present invention, a negative electrode is provided, which is obtained by coating a negative electrode slurry on a negative electrode current collector and then drying and compacting the negative electrode slurry in sequence, wherein the negative electrode slurry is the aforementioned lithium titanate slurry.

[0014] According to another aspect of the present invention, a lithium ion battery is provided, comprising a negative electrode, a positive electrode and a separator, wherein the negative electrode is the negative electrode mentioned above.

[0015] Applying the technical solution of the present invention, the present application performs a first mechanical stirring of the raw materials including a binder, a conductive agent and lithium titanate, with the purpose of premixing the first mixture uniformly. The raw materials of the first mixture and the solvent are subjected to a second mechanical stirring, with the purpose of fully wetting the obtained second mixture. Then, a centrifugal mixer is used for high-speed stirring, and the material is forcibly squeezed onto the container wall by centrifugal force, forming a thin film that rotates at high speed, generating a huge shear force to disperse and refine the material particles, and achieving a uniform dispersion effect in a short time, thereby solving the problem of the difficulty in dispersing the nano lithium titanate material, and effectively shortening the time of the stirring process, improving the stability of the lithium titanate slurry, and thus improving the quality stability of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 The graph showing the change in viscosity of the lithium titanate slurry obtained in Example 1 and Comparative Example 1 of the present application over time is shown. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0019] As analyzed in the background technology of this application, there is a problem in the prior art that the quality of the electrode is unstable due to the poor dispersibility and stability of the negative electrode slurry. In order to solve the above problem, this application provides a lithium titanate slurry and a preparation method thereof, a negative electrode and a lithium-ion battery.

[0020] In a typical embodiment of the present application, a method for preparing a lithium titanate slurry is provided, the preparation method comprising: subjecting a raw material including a binder, a conductive agent and lithium titanate to a first mechanical stirring to obtain a first mixture; subjecting a raw material including the first mixture and a solvent to a second mechanical stirring to obtain a second mixture; and subjecting the second mixture to centrifugal stirring to obtain a lithium titanate slurry.

[0021] The present application subjects the raw materials including a binder, a conductive agent and lithium titanate to a first mechanical stirring, the purpose of which is to premix the first mixture evenly. The raw materials of the first mixture and the solvent are subjected to a second mechanical stirring, the purpose of which is to fully wet the obtained second mixture. A centrifugal mixer is then used for high-speed stirring, and the material is forcibly squeezed onto the container wall by centrifugal force, forming a thin film that rotates at high speed, generating a huge shear force to disperse and refine the material particles, achieving a uniform dispersion effect in a short time, thereby solving the problem of the difficulty in dispersing nano lithium titanate materials, and effectively shortening the time of the stirring process, improving the stability of the lithium titanate slurry, and thereby improving the quality stability of the pole piece.

[0022] In one embodiment of the present application, the rotation speed of the first mechanical stirring is 500-1000 rpm, and the time of the first mechanical stirring is 0.5-1 h.

[0023] By controlling the rotation speed of the first mechanical stirring to 500-1000 rpm and the time of the first mechanical stirring to 0.5-1 h, it helps to ensure that the first mixture is premixed uniformly, effectively shortens the stirring process time, and is conducive to continuous production.

[0024] In one embodiment of the present application, the rotation speed of the second mechanical stirring is 1500-2000 rpm, and the time of the second mechanical stirring is 1-2 hours.

[0025] By controlling the rotation speed of the second mechanical stirring to 1500-2000rpm and the time of the second mechanical stirring to 1-2h, it helps to ensure that the second mixture is fully wetted, effectively shortens the stirring process time, improves the stability of the slurry, and is conducive to continuous production.

[0026] In one embodiment of the present application, the rotation speed of the centrifugal stirring is 2500-3000 rpm, and the time of the centrifugal stirring is 3-5 hours.

[0027] The present application adopts a centrifugal stirring process and controls the rotation speed of the centrifugal stirring within the above-mentioned range, which helps to utilize centrifugal force to rotate the slurry at high speed, generate huge shear force to disperse and refine the particles, thereby achieving a uniform dispersion of the lithium titanate slurry in a short time, thereby effectively shortening the stirring process time and facilitating continuous production.

[0028] In one embodiment of the present application, the mass ratio of the above-mentioned binder, conductive agent and lithium titanate is 2.5% to 5%: 2.5% to 5%: 90% to 95%; and / or the conductive agent is selected from any one or more of carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, graphene, and / or the solvent is N-methyl-2-pyrrolidone, and / or the binder is selected from any one or more of PVDF, PTFE and acrylonitrile; and / or the solid content of the lithium titanate slurry is 50 to 60%.

[0029] It is preferred to control the mass ratio of the binder, the conductive agent and the lithium titanate within the above range, which is beneficial to improve the synergistic effect between the components and obtain a lithium titanate battery slurry with excellent electrical properties, so that the electrode sheet prepared by the conductive slurry can have a suitable internal resistance and the battery using the electrode sheet has a suitable battery capacity. The preferred conductive agent above is beneficial to improve the conductivity of the electrode material, thereby improving the charge and discharge performance and cycle stability of the battery. The preferred solvent above is beneficial to improve the dispersibility of the binder in the solvent, so that the conductive agent, lithium titanate and the solvent are mixed to form a stable and uniform slurry. The preferred binder above, on the one hand, can reduce the use of PVDF while ensuring the cycle life of the battery, thereby increasing the battery capacity, and on the other hand, effectively improves the viscosity problem in the slurrying process, and improves the rate performance of the battery. Controlling the solid content of the lithium titanate slurry within the above range helps to ensure that the viscosity of the lithium titanate slurry is within a suitable range, thereby improving the uniform dispersion and stability of the lithium titanate slurry while improving its coatability.

[0030] In one embodiment of the present application, the preparation method further includes adjusting the viscosity and fineness of the lithium titanate slurry.

[0031] Further control of the viscosity and fineness of the lithium titanate battery slurry is beneficial to improving the uniform dispersion and stability of the lithium titanate slurry, thereby improving the operability of the negative electrode slurry in the electrode coating and improving the electrical properties of the entire lithium titanate battery slurry.

[0032] In another typical embodiment of the present application, a lithium titanate slurry is provided, and the lithium titanate slurry is prepared by the above-mentioned preparation method.

[0033] The lithium titanate slurry obtained by the above preparation method has high stability, which helps to improve the quality stability of the pole piece.

[0034] In some embodiments of the present application, the viscosity of the lithium titanate slurry is 8000-15000 mPa·s, and / or the viscosity of the lithium titanate slurry after standing for 10-12 hours is 20000-40000 mPa·s, and / or the fineness of the lithium titanate slurry is 25-35 μm.

[0035] The preferred lithium titanate slurry is more suitable for use as negative electrode slurry, thereby helping to improve the quality and performance of the negative electrode sheet.

[0036] In another typical embodiment of the present application, a negative electrode is provided, which is obtained by coating a negative electrode slurry on a negative electrode current collector and then drying and compacting the negative electrode slurry in sequence, wherein the negative electrode slurry is the above-mentioned lithium titanate slurry.

[0037] Since the aforementioned lithium titanate slurry has high uniformity and stability, the negative electrode of the present application has high electrical performance.

[0038] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a negative electrode, a positive electrode and a separator, wherein the negative electrode is the negative electrode described above.

[0039] The lithium ion battery including the negative electrode of the present application has excellent electrical properties.

[0040] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0041] Example 1

[0042] The first step: a certain proportion of binder (PVDF), acetylene black, and lithium titanate material are subjected to the first mechanical stirring in a mechanical stirrer. The speed of the first mechanical stirring is 1000 rpm, and the time of the first mechanical stirring is 0.5 h to obtain a first mixture. The mass ratio of binder (PVDF), acetylene black and lithium titanate material is 5%:5%:90%.

[0043] Step 2: Add 1000 mL of solvent (NMP) into the first mixture for second mechanical stirring (in a mechanical stirrer). The rotation speed of the second mechanical stirring is 2500 rpm and the time of the second mechanical stirring is 1.5 h, so that the material is fully wetted to obtain a second mixture.

[0044] Step 3: The second mixture is centrifugally stirred using a centrifugal mixer at a speed of 3000 rpm for 4 hours to obtain lithium titanate slurry.

[0045] Step 4: Test the viscosity and fineness of the lithium titanate slurry in the third step, adjust the viscosity of the slurry, and complete the slurrying. The viscosity of the lithium titanate slurry is 9090 mPa·s, the solid content is 52%, and the fineness of the lithium titanate slurry is 32 μm.

[0046] Example 2

[0047] The difference from Example 1 is that the rotation speed of the first mechanical stirring is 800 rpm, the time of the first mechanical stirring is 1 hour, and the first mixture is obtained, and finally the lithium titanate slurry is obtained.

[0048] Example 3

[0049] The difference from Example 1 is that the rotation speed of the first mechanical stirring is 400 rpm, the time of the first mechanical stirring is 1.5 h, and the first mixture is obtained, and finally the lithium titanate slurry is obtained.

[0050] Example 4

[0051] The difference from Example 1 is that the rotation speed of the second mechanical stirring is 2000 rpm, the time of the second mechanical stirring is 1.5 hours, and the second mixture is obtained, and finally the lithium titanate slurry is obtained.

[0052] Example 5

[0053] The difference from Example 1 is that the rotation speed of the second mechanical stirring is 1300 rpm, the time of the second mechanical stirring is 1 hour, and the second mixture is obtained, and finally the lithium titanate slurry is obtained.

[0054] Example 6

[0055] The difference from Example 1 is that the rotation speed of the centrifugal stirring is 2800 rpm, the time of the centrifugal stirring is 4 hours, and finally a lithium titanate slurry is obtained.

[0056] Example 7

[0057] The difference from Example 1 is that the rotation speed of the centrifugal stirring is 2400 rpm, the time of the centrifugal stirring is 3.5 h, and finally a lithium titanate slurry is obtained.

[0058] Example 8

[0059] The difference from Example 1 is that the mass ratio of PVDF, acetylene black and lithium titanate material is 4%:4%:92%, and finally a lithium titanate slurry is obtained. The viscosity of the lithium titanate slurry is 8500mPa·s, the solid content is 53%, and the fineness of the lithium titanate slurry is 32μm.

[0060] Example 9

[0061] The difference from Example 1 is that the mass ratio of PVDF, acetylene black and lithium titanate material is 5.2%:2.8%:92%, and finally a lithium titanate slurry is obtained. The viscosity of the lithium titanate slurry is 12100 mPa·s, the solid content is 53%, and the fineness of the lithium titanate slurry is 35 μm.

[0062] Comparative Example 1

[0063] The first step: stir a certain proportion of binder (PVDF) and solvent (NMP) at a stirring speed of 1000 rpm for 6 hours to obtain a glue solution.

[0064] Step 2: Stir a certain proportion of acetylene black with the glue prepared in the first step at a stirring speed of 2500 rpm for 4 hours to obtain a conductive glue.

[0065] Step 3: Stir a certain proportion of lithium titanate material with the conductive adhesive prepared in the second step at a stirring speed of 2500 rpm for 6 hours to obtain lithium titanate slurry.

[0066] Step 4: Test the viscosity and fineness of the lithium titanate slurry in the third step, adjust the slurry viscosity, and complete the slurrying. The viscosity of the lithium titanate slurry is 9080 mPa·s, the solid content is 51.2%, and the fineness of the lithium titanate slurry is 30 μm.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that, in the third step: subjecting the second mixture to a third mechanical stirring, the rotation speed of the mechanical stirring is 3000-3500 rpm, and the centrifugal stirring time is 3 hours, to obtain lithium titanate slurry.

[0069] Comparing the two slurry preparation methods, the conventional wet stirring (Comparative Example 1) takes 15 to 16 hours to make the lithium titanate material dispersed evenly. The premixing + centrifugal stirring process of the embodiment of the present application uses centrifugal force to rotate the slurry at high speed, generating huge shear force to disperse and refine the particles, achieving a uniform dispersion effect in a short time. The stirring process time is 4 to 5 hours, which effectively shortens the process time and is conducive to continuous production.

[0070] Static viscosity tests were performed on the slurries prepared by the above two lithium titanate slurry preparation methods. The same viscosity rotor and rotation speed were used to evaluate the stability of the lithium titanate slurry. The test results are shown in Table 1 below. The viscosity change curves of the lithium titanate slurries obtained in Example 1 and Comparative Example 1 over time are shown in Table 1. Figure 1 As shown. Figure 1 It can be seen that the static viscosity change of the lithium titanate slurry prepared in Example 1 is smaller than that of the comparative example, that is, the stability of the lithium titanate slurry prepared in Example 1 is better.

[0071] The changes in viscosity of the lithium titanate slurries obtained in the remaining examples and comparative examples over time are listed in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0076] The present application subjects the raw materials including a binder, a conductive agent and lithium titanate to a first mechanical stirring, the purpose of which is to premix the first mixture evenly. The raw materials of the first mixture and the solvent are subjected to a second mechanical stirring, the purpose of which is to fully wet the obtained second mixture. A centrifugal mixer is then used for high-speed stirring, and the material is forcibly squeezed onto the container wall by centrifugal force, forming a thin film that rotates at high speed, generating a huge shear force to disperse and refine the material particles, achieving a uniform dispersion effect in a short time, thereby solving the problem of the difficulty in dispersing nano lithium titanate materials, and effectively shortening the time of the stirring process, improving the stability of the lithium titanate slurry, and thereby improving the quality stability of the pole piece.

[0077] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing lithium titanate slurry, characterized in that: The preparation method comprises: Subjecting the raw materials including the binder, the conductive agent and the lithium titanate to a first mechanical stirring to obtain a first mixture; subjecting the raw material including the first mixture and the solvent to a second mechanical stirring to obtain a second mixture; The second mixture is centrifugally stirred to obtain lithium titanate slurry.

2. The preparation method according to claim 1, characterized in that: The rotation speed of the first mechanical stirring is 500-1000 rpm, and the time of the first mechanical stirring is 0.5-1 h.

3. The preparation method according to claim 1 or 2, characterized in that: The rotation speed of the second mechanical stirring is 1500-2000 rpm, and the time of the second mechanical stirring is 1-2 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The rotation speed of the centrifugal stirring is 2500-3000 rpm, and the time of the centrifugal stirring is 3-5 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the binder, the conductive agent and the lithium titanate is 2.5% to 5%: 2.5% to 5%: 90% to 95%; and / or the conductive agent is selected from any one or more of carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, and graphene, and / or the solvent is N-methyl-2-pyrrolidone, and / or the binder is selected from any one or more of PVDF, PTFE and acrylonitrile; and / or the solid content of the lithium titanate slurry is 50 to 60%.

6. The preparation method according to any one of claims 1 to 5, characterized in that The preparation method also includes adjusting the viscosity and fineness of the lithium titanate slurry.

7. A lithium titanate slurry, characterized in that: The lithium titanate slurry is prepared by the preparation method according to any one of claims 1 to 6.

8. The lithium titanate slurry according to claim 7, characterized in that: The viscosity of the lithium titanate slurry is 8000-15000 mPa·s, and / or the viscosity of the lithium titanate slurry after standing for 10-12 hours is 20000-40000 mPa·s, and / or the fineness of the lithium titanate slurry is 25-35 μm.

9. A negative electrode, obtained by coating a negative electrode slurry on a negative electrode current collector, followed by drying and compacting, characterized in that: The negative electrode slurry is the lithium titanate slurry according to claim 7 or 8.

10. A lithium ion battery comprising a negative electrode, a positive electrode and a separator, characterized in that: The negative electrode is the negative electrode according to claim 9.